On the correct holotype and type locality of Cercomacra sclateri Hellmayr 1905 (Aves: Thamnophilidae) - Cavarzere, Vagner; Lecroy, Mary; Marcondes, Rafael Sobral; Da Costa, Thiago Vernaschi Vieira; Silveira, Luís Fábio (Zootaxa, 2012)
Cercomacra cinerascens Hellmayr 1905 is a medium-sized species of antbird distributed throughout the Amazon Basin in South America. It comprises a complex of four currently recognized taxa, C. c. cinerascens (Sclater 1857), C. c. immaculata Chubb 1918, C. c. sclateri Hellmayr 1905 and C. c. iterata Zimmer 1932, all characterized by the grey coloration of males and brownish olive coloration of females, long and graduated white-tipped tails, hidden white interscapular patch and distinct stiff rictal bristles. All subspecies primarily inhabit unflooded terra firme forests, the former two occurring north of the Rio Amazonas and the latter two in southern Amazonia (Fig. 1, Zimmer & Isler 2003).